Pesan Dakwah Gus Murobbi Binnur di Channel Youtube Persada TV PPSD - Argo Saputro; Sutopo Sutopo (An-Nashiha: Journal of Broadcasting and Islamic Comunication Studies, 2022)
The focus of the problem in this research is What are Gus Murobbi Binnur's Da'wah Messages on the Persada TV PPSD YouTube Channel March 2021 Edition which contains Aqidah, Sharia and Akhlaq. This study uses descriptive qualitative research methods. obtained through the results of observations, observations (observations), interviews (interviews) and documentation. As well as using content analysis techniques to analyze the data. The presentation of data from this study uses a content analysis format with the aim of describing, summarizing what is on the record of the Persada TV PPSD YouTube Channel. From the results of the study, it can be concluded that what is the message of Gus Murobbi Binnur's Da'wah on the Persada TV PPSD YouTube Channel March 2021 Edition. It can be concluded into three categories, namely the creed of the da'wah message conveyed by Gus Murobbi Binnur in the category of creed, more about the true nature of the case. is the destiny of Allah SWT, as well as explaining about all trials that come from Allah SWT. Da'wah messages in the moral category In the moral category, Gus Murobbi Binnur explains moral values to himself, to fellow humans and to God. When there is a dispute, do not blame each other, because we should not blame the High Priest. When a servant asks for worldly matters, he will not be rich, but on the contrary, he will be poor with many trials. Da'wah messages in the sharia category In this category, Gus Murobbi Binnur mostly gives da'wah messages in the form of suggestions to be more careful with the current media such as tiktok, which if used incorrectly will result in a jariyyah sin. Then he advised to stay away from video calls with the opposite sex who is not a mahrom, because it is like meeting face to face in Islam is prohibited, and he advised to stay away from such things.